Pendidikan Multikultural dan Inklusi - Yuniarti; Amini, Sri Aisyah; Jumadil Ranto Mulia; Ridwal Trisoni (Jurnal Dirosah Islamiyah, 2024)
This research aims to explore and describe the types of educational policies and programs made by the government, especially regarding multicultural education policies and inclusive education. Multicultural education is implemented to develop all students' potential regardless of their religion. Multicultural education emphasizes the philosophy of cultural pluralism in the education system, based on the principles of equality, mutual respect, acceptance, understanding and moral commitment to social justice. Meanwhile, inclusive education accommodates all children with special needs who have a normal IQ, intended for those who have disabilities, special talents, special intelligence and/or who require special educational services. The foundation of inclusive education is the Law on the National Education System chapter IV article V concerning the rights and obligations of citizens. The method used in this research is a type or library approach (Library Research). The data collection technique used in this research is a document technique, namely searching for information about the topics discussed in the form of notes, books, publications or articles, magazines, etc.